Sleep efficiency and event−related potentials in patients with depression: the mediating role of serum C-reactive protein - Fang, Liang; Wang, Peng; Xie, Tianqin; Ding, Shuai; Wang, Ting; Zhang, Jiajia; Zhang, Aiguo; Zhu, Peng; Zhu, Daomin (Frontiers in Psychiatry, 2025)
BackgroundPatients with major depressive disorder (MDD) may experience cognitive dysfunction and sleep disorders. Limited research exists on the neurophysiological mechanisms that connect sleep efficiency and cognitive function in individuals with MDD. The study aims to investigate the link between sleep efficiency, mental abilities, and levels of serum C-reactive protein (CRP) in individuals diagnosed with MDD.MethodsA total of 101 individuals diagnosed with MDD were selected and categorized into two groups: the normal sleep efficiency group (NSE) with SE ≥90% and the group with lower sleep efficiency (LSE) with SE <Eth) All patients underwent polysomnography (PSG), event-related potentials (ERPs) tests, and CRP detection. The study used multiple linear regression and bootstrapped mediation analysis to explore the correlation between SE, ERPs latency, and CRP.ResultsThe N2, P3a, and P3b latencies were longer in the LSE group compared to the NSE group (p = 0.036, p = 0.013, p < 0.001). N2 (Pr = -122.182), P3a (Pr = -109.597), P3b (Pr = -151.960), and CRP (Pr = -3.768) are significantly associated with SE. A strong correlation was found between CRP (Pr = 9.414) and P3b latency. After controlling for gender and other pertinent variables, the subsequent investigation revealed a direct correlation between CRP and P3b latency, specifically within the cohort of depression patients exhibiting low SE. CRP mediated the association between SE and P3b latency.ConclusionLow SE with MDD was associated with chronic inflammation and impaired cognitive function, suggesting that inflammation may act as a potential mediating factor in the relationship between SE and impaired cognitive function.